Quality and Shelf Life of Dragon Fruit (Hylocereus costaricensis) with Edible Coating of Watermelon Albedo Pectin with Addition of Ginger Extract (Zingiber officinale) - Virda, Virda Yurniar; Asra, Revis; Adriadi, Ade (Biospecies, 2024)
Dragon fruit (Hylocereus sp.) is a horticultural commodity that has bright prospects in the agricultural sector. Dragon fruit is a perishable and rotten fruit. Efforts are made by coating (edible coating). This study aims to determine the quality and shelf life of dragon fruit with edible coating of watermelon albedo pectin with the addition of ginger extract. This research was conducted in March-April 2022. The results of the study stated that the edible coating of watermelon albedo pectin with the addition of ginger extract had no effect on fruit quality on weight loss and water content and the best concentration of ginger extract on edible coating of watermelon albedo pectin, namely the concentration of ginger extract 54% on the texture and color of the neutral fruit ( 3) on 14 days storage.